Perillaldehyde synergizes with ferroptosis inducers to promote ferroptotic cell death in gastric cancer - Rui Wang; Jin-Feng Cui; Jing Lv; Jia-Lin Song; Yang-Yang Lu; Xiao-Juan Huang; Zhong-Kun Lin; Zhong-Kun Lin; Si-Yi Zhang; Sha-Sha Wang; Wen-Sheng Qiu (Frontiers in Cell and Developmental Biology)
IntroductionAs a traditional medicine and food homologous plant, Perilla frutescens is widely cultivated in China, Japan, and Korea. According to the Compendium of Materia Medica, the leaves, stems, and seeds of perilla can all be used as medicine. Perilla essential oil has been used in traditional Chinese medicine since ancient times. It has been demonstrated that perillaldehyde (PAH), a primary composition of the essential oil extracted from perilla, can inhibit tumor growth through multiple mechanisms. However, the specific mechanisms by which PAH suppresses gastric cancer remain incompletely understood.MethodsWe performed in vitro experiments using three cell lines (AGS, HGC27, and MFC) to assess the effects of PAH on cell viability, proliferation, and migration of gastric cancer cells. Concurrently, we established a subcutaneous gastric tumor model in BALB/c nude mice for in vivo animal studies. Subsequently, oxidative stress was measured via fluorescence staining techniques (H2DCFDA, DHE, and JC-1). We then evaluated whether PAH induced ferroptosis in gastric cancer cells through FerroOrange staining, quantification of intracellular glutathione (GSH) and lipid peroxidation levels, and Western blotting. Finally, PAH was co-administered with the ferroptosis inhibitor Ferrostatin-1 (Fer-1) or the ferroptosis inducer RSL3, and relevant experiments were re-evaluated.ResultsIn this study, PAH was proven to inhibit the growth of gastric cancer both in vivo and in vitro. It led to a reduction in mitochondrial membrane potential (MMP), an augmentation of the accumulation of reactive oxygen species (ROS), and an elevation of oxidative stress levels. Moreover, PAH decreased intracellular GSH levels while increasing intracellular lipid peroxidation and Fe2+ levels. These effects indicate that PAH induces ferroptosis via inhibiting the system Xc (−)/GSH/GPX4 axis. Furthermore, PAH influenced the expression of proteins related to iron transport and storage and regulated ferroptosis via the P62-Keap1-Nrf2 pathway. When combined with the ferroptosis inducer RSL3, PAH could promote ferroptosis in gastric cancer.DiscussionOur research suggests a potential therapeutic strategy in which PAH could be used to synergize with ferroptosis inducers for treating gastric cancer.